Onthel Sebagai Ide Penciptaan Dalam Karya Seni Grafis - Dewi Ildami Hasibuan; Irwan Irwan (Universitas Katolik Widya Karya Malang, 2023)
The purpose of the Final Project is to visualize the classic onthel bicycle in the development of the times as an idea for the creation of graphic works in serigraphy technique with a combination method, colet method, afdruk method and cut pattern method. The method of creation carried out in the final work has stages from the beginning of the process to the end, namely the preparation, elaboration, synthesis, concept realization, and completion or finishing stages in the work. In the process of making the final work measuring 69 cm x 49cm using serigraphy on canvas, there are 10 pieces with titles namely: Renewal, Communication, Trend, Sad, Driver, Influence, Obstacle, Identity, Message, and Consistent.